Genetic diversity analysis among Indian goat breeds based on mitochondrial DNA - SHARMA, ANURODH; SINGH, KARAN VEER; SIVALINGAM, JAYAKUMAR; P, MANIMOHAN; SAROHA, VINITA; RAVIKUMAR, D; KUMAR, DINESH; DIXIT, S P (The Indian Journal of Animal Sciences, 2020)
India ranks second in goat population with 34 genetically recognized and registered breeds. Information on their diversity and origin and ancestry is little known. Hence, the mtDNA based genetic diversity analysis of Indian goats; targeting mitochondrial HVR1 region from 21 Indian breeds belonging to different geographical regions was undertaken. A total of 124 haplotypes were identified and haplotype diversity estimate ranged from 0.67 to 1.0 with an average value of 0.99. The average nucleotide diversity was minimum (0.02) in Kanniadu and maximum in Surti breeds. Analysis of molecular variance revealed 5.16% variation among the breeds and 94.84% within breeds indicating weak phylogeographic structure. Neighbor-joining tree analysis revealed that the maximum number of individuals of Indian goats fall under A and few in B and C lineages. Principal component analyses of the Indian goat breeds revealed that Kanniadu goats clustered distantly from rest of the breeds of the country. Mantel test revealed a significant correlation between FST and geographical distance (r=0.29) among the goat breeds. The mismatch distribution analysis of the Indian goat breeds revealed bimodal distribution patterns. The analysis revealed that Kanniadu is highly distinct from the rest of the breeds.